2016
DOI: 10.1159/000441657
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Neuropsychological Correlates in Positive and Negative Formal Thought Disorder Syndromes: The Thought and Language Disorder Scale in Endogenous Psychoses

Abstract: The correlation of formal thought disorder (FTD) symptoms and subsyndromes with neuropsychological dimensions is as yet unclear. Evidence for a dysexecutive syndrome and semantic access impairments has been discussed in positive FTD, albeit focusing mostly on patients with schizophrenia. We investigated the correlation of the full range of positive and negative as well as subjective and objective FTD with neuropsychological domains in different patient groups. Patients with ICD-10 schizophrenia (n = 51), depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 32 publications
5
28
0
4
Order By: Relevance
“…Given the importance of FTD in defining the nature of psychosis and predicting its clinical (Demjaha et al, 2017) and global functional impact (Cavelti et al, 2016), one must be able to relate such a measure to functional outcome as well as any existing scales for FTD. The measure should also be expected to relate to core cognitive deficits in psychoses such as processing speed (Dickinson et al, 2007), as FTD shows a complex interplay with cognitive impairment (Xu et al, 2014;Nagels et al, 2016). Finally, this measure can also be expected to relate to functional and structural measures of neuroanatomical measures.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of FTD in defining the nature of psychosis and predicting its clinical (Demjaha et al, 2017) and global functional impact (Cavelti et al, 2016), one must be able to relate such a measure to functional outcome as well as any existing scales for FTD. The measure should also be expected to relate to core cognitive deficits in psychoses such as processing speed (Dickinson et al, 2007), as FTD shows a complex interplay with cognitive impairment (Xu et al, 2014;Nagels et al, 2016). Finally, this measure can also be expected to relate to functional and structural measures of neuroanatomical measures.…”
Section: Introductionmentioning
confidence: 99%
“…Most ICD-9 and ICD-10 codes were available through the Chronic Conditions Data Warehouse. 14 For those that were not, we looked to published studies on similar populations [17][18][19][20][21][22][23][24][25][26][27][28] and mapped equivalent diagnoses between ICD-9 and ICD-10 (Online Appendix Table 2). When creating the eligible population, we looked at all Part A and Part B claims for each beneficiary from January 1, 2013, to June 30, 2015, and included all conditions that matched the diagnosis codes in Online Appendix Table 2.…”
Section: Creation Of the Eligible Populationmentioning
confidence: 99%
“…Since the ability to understand and make use of figurative language may be altered in various disorders (Benítez-Burraco, 2017 ), clinical populations “offer a glimpse into subtle dissociations between literal and non-literal (figurative) language” (Vulchanova et al, 2015 , p. 4). Dysfunctions in figurative language processing are commonly found in clinical populations such as ASD (e.g., Happé, 1995 ), Williams syndrome (Annaz et al, 2009 ), schizophrenia (e.g., Mossaheb et al, 2014 ), and major depression (Nagels et al, 2016 ). Moreover, an association was found between formal thought disorder (FTD) symptom severity in patients with depression and performance in a multiple-choice proverb test: a subcategorization into different FTD dimensions such as positive (e.g., derailment, crosstalk, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…and negative symptoms (e.g., poverty of thought, inhibited thinking, etc.) revealed that the negative dimension was related to proverb interpretation performance (Nagels et al, 2016 ). To date it is unclear how different FTD dimensions are associated to the use of internal state language in spontaneous speech.…”
Section: Introductionmentioning
confidence: 99%